(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. This study was conducted to compare catheter function, dialysis adequacy, and dialysis-related complications among patients receiving long-term dialysis via Palindrome catheter, Permcath catheter, and arteriovenous fistula (AVF) as vascular access. Materials and Methods. Forty-three patients undergoing dialysis with Permcath catheter, 49 with Palindrome catheter, and 56 with AVF were recruited. Urea clearance (KT/V), urea reduction rate, and the highest blood flow at the arteriovenous junction during dialysis were determined during the dialysis sessions. Catheter-related infection, catheter-associated thrombosis, and annual patency rate were also evaluated. Results. In patients using Permcath catheter for dialysis, the incidence of secondary renal injury (metabolic diseases, hypertension, and ischemic kidney diseases) was 73.1%, which was significantly higher than that in patients with AVF (51.5%; P < .001). In the Palindrome group, maximum blood flow, KT/V, urea reduction rate, and annual patency rate were significantly higher than those in the Permcath group, and the incidence of access-related infection was significantly higher than that in the AVF group. In the Palindrome group, the prevalence of thromboembolism was 30.6%, which was significantly lower than that in the Permcath group (46.5%), but higher than that in the AVF group (5.4%). Conclusions. For dialysis patients, Palindrome catheter was superior to Permcath catheter and comparable with the AVF in terms of the maximum blood flow, dialysis adequacy, and annual patency rate. Dialysis with Palindrome catheter has a high infection rate and a high incidence of thromboembolism as in the dialysis with Permcath catheter.